SEBARAN DAERAH PENANGKAPAN BAGAN PERAHU DI SAMUDERA HINDIA - Rahmani, Ratih Martia; Sarianto, Deni; Tashwir, Tashwir; Syamson, Indra; Rosano, Zalmi; Mesenu, Mesenu; Aisyah, Siti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Fishing areas have long been used by fishermen to determine the potential or not of a body of water. Mapping of fishing areas is often forgotten by fishermen in determining whether or not an area has the potential to be targeted. This research aims to map fishing areas using fishing gear and the types of fish caught in the Indian Ocean. This research was carried out in the waters of the Mentawai Islands and Tiku waters, West Sumatra Province. The research results show that there are three fishing areas in the Indian Ocean, namely (1) Siberut Island Zone, (2) Siberut Tiku Inter-Island Zone and (3) Tiku Zone. The main catch was 16 types of fish which were the target catch. The biggest catches are mackerel, Gymnocranius griseus and Carangoides armatus. The smallest catch is anchovies. With such a small catch of anchovies, it can be said that Bagan is no longer the main target for anchovies. This change was caused by the difficult fishing areas for anchovies and the cheap selling prices for anchovies.Keyword: Catch, Fishing ground, Mapping, Zone, SustainabilityAbstrak: Daerah penangkapan telah lama digunakan oleh para nelayan untuk menentukan potensial atau tidak suatu perairan. Pemetaan daerah penangkapan seringkali dilupakan oleh nelayan dalam menentukan potensial atau tidaknya suatu perairan yang akan dijadikan sasaran penangkapan. Penelitian ini bertujuan untuk memetakan daerah penangkapan dengan alat tangkap bagan dan jenis ikan yang tertangkap di Samudera Hindia. Penelitian ini dilaksanakan di Perairan Kepulauan Mentawai dan Perairan Tiku, Propinsi Sumatera Barat. Hasil penelitian menunjukkan bahwa terdapat tiga wilayah daerah penangkapan di Samudera Hindia yaitu (1) Zona Pulau Siberut, (2) Zona antar Pulau Siberut Tiku dan (3) zona Tiku. Hasil tangkapan utama diperoleh sebanyak 16 jenis ikan yang menjadi target tangkapan. Tangkapan terbanyak adalah ikan kembung, gulamah, dan kuwe. Tangkapan paling sedikit adalah ikan teri. Dengan hasil tangkapan teri yang sedikit dapat dikatakan bahwa bagan bukan lagi target utamanya ikan teri. Perubahan ini disebabkan oleh daerah penangkapan ikan teri susah makin susah dan harga jual ikan teri yang semakin murah.Kata kunci: Daerah tangkapan, Hasil tangkapan, Keberlanjutan, Pemetaan, Zona